Working Memory for Linguistic and Non-linguistic Manual Gestures: Evidence, Theory, and Application - Rudner, Mary (Frontiers in Psychology, 2018)
Linguistic manual gestures are the basis of sign languages used by deaf individuals. Working memory and language processing are intimately connected and thus when language is gesture-based, it is important to understand related working memory mechanisms. This article reviews work on working memory for linguistic and non-linguistic manual gestures and discusses theoretical and applied implications. Empirical evidence shows that there are effects of load and stimulus degradation on working memory for manual gestures. These effects are similar to those found for working memory for speech-based language. Further, there are effects of pre-existing linguistic representation that are partially similar across language modalities. But above all, deaf signers score higher than hearing non-signers on an n-back task with sign-based stimuli, irrespective of their semantic and phonological content, but not with non-linguistic manual actions. This pattern may be partially explained by recent findings relating to cross-modal plasticity in deaf individuals. It suggests that in linguistic gesture-based working memory, semantic aspects may outweigh phonological aspects when processing takes place under challenging conditions. The close association between working memory and language development should be taken into account in understanding and alleviating the challenges faced by deaf children growing up with cochlear implants as well as other clinical populations.